THE INFLUENCE OF USING SQP2RS (SURVEY, QUESTION, PREDICT, READ, RESPOND, SUMMARIZE) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Jusak Patty (JURNAL TAHURI, 2021)
Reading is the foundation that supports the success of academic achievement and hence it should be given top priority. The objective of this study was to find out the influence of using SQP2RS strategy towards students’ reading comprehension. This study was a pre experiment research using one-group pretest – posttest design. The sample of this study consisted of 38 students of XI Science grade of SMA N 2 Ambon, which was selected purposely. The data was collected by using an essay test and analysed statically. The results showed there was a positive and significant influence of using SQP2RS strategy toward students reading comprehension